68.5k views
19 votes
Solve the equation a/a^2-9 +3/a-3=1/a+3

User SheetJS
by
5.0k points

1 Answer

3 votes
Answer is: a= -4
STEP
1
:

1
Simplify —————
a + 3
Equation at the end of step
1
:

a 3 1
(————————+—————)-——— = 0
((a2)-9) (a-3) a+3
STEP
2
:

3
Simplify —————
a - 3
Equation at the end of step
2
:

a 3 1
(————————+———)-——— = 0
((a2)-9) a-3 a+3
STEP
3
:

a
Simplify ——————
a2 - 9
Equation at the end of step
3
:

a 3 1
(————————————————— + —————) - ————— = 0
(a + 3) • (a - 3) a - 3 a + 3

Equation at the end of step
4
:

(4a + 9) 1
————————————————— - ————— = 0
(a + 3) • (a - 3) a + 3
Pull out like factors :

3a + 12 = 3 • (a + 4)

Equation at the end of step
6
:

3 • (a + 4)
————————————————— = 0
(a + 3) • (a - 3)

3•(a+4)
——————————— • (a+3)•(a-3) = 0 • (a+3)•(a-3)
(a+3)•(a-3)

a+4 = 0

Subtract 4 from both sides of the equation :
a = -4
User Marvin Correia
by
5.3k points